Sustainable management of end-of-life creosote-treated wood poles sawdust into red ceramics for environmental and health protection - Spiliotis, X.; Karastergiou, S.; Lalas, S.; Athanasiadis, V.; Lakioti, E.; Papapolymerou, G.; Karayannis, Vayos (Technical Annals, 2023)
In the current original research, sintered red ceramics, incorporated with creosote-impregnated timber (CIT) in the form of sawdust as a useful porous making additive, were manufactured and characterized. Actually, safe management of creosote-treated electricity and telecommunication poles waste and its utilization as a useful secondary raw material into materials of added-value, represents an important priority towards circular economy and equally a great challenge given potential health risks reported in association with reuse of creosote-containing materials. The full life cycle of creosote-treated electricity and telecommunication poles includes: the growth of trees on forested land, harvest of logs, milling to produce poles and lumber; then creosote treatment of poles and their use by the Electricity and Telecommunication Grids; and finally disposal in landfills or valorization as an energy source at the end of their use lives. This paper reports results of evaluation performed to determine the possibility of using end-of-life poles in the form of sawdust as additive (pore making agent) in building ceramic industry. End of Waste (EoW) criteria will be implemented to assess the safe use of this waste by-product as secondary resource, for ensuring environmental and human health protection.